peran, kader, posyandu PERAN KADER KESEHATAN DALAM PELAYANAN POSYANDU UPTD PUSKESMAS KECAMATAN SANANWETAN KOTA BLITAR - Sunarti Poltekkes Kemenkes Malang (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2018)
Abstract Health cadres is voluntary power chosen the community and have duty to develop the community who were recruited from, by, for, the community, the existence of cadres often associated with service in posyandu to help smooth health service. Research purposes describe the role of healthcare in service at Posyandu UPTD Puskesmas Sananwetan District Blitar City. Research methods use design descriptive. The population are 44 health cadres, with purposive sampling. Data collection using questionnaires and observations. The results of most of the cadres 77,3% Categorized well A small part of the cadre 18,2% Categorized enough, Health volunteers have a good role preparing the equipment of posyandu before posyandu start, Prepare additional food for babies and toddlers, Reporting on all activities undertaken and lacking in working on a five-posyandu table system. Posyandu program holders can conduct further training and conduct socialization or evaluation every year to increase the independence of cadres in providing health services in accordance with the posyandu service flow table I to table V. Keywords: role, healthcare, posyandu.